2021
DOI: 10.1163/1568539x-bja10103
|View full text |Cite
|
Sign up to set email alerts
|

Aggression towards neonates and possible infanticide in the boto, or Amazon river dolphin (Inia geoffrensis)

Abstract: Recent observed attacks by male Amazon river dolphins on conspecific calves, together with post-mortem examinations, indicate that infanticide occurs in this species but that not all attacked calves are killed. If mortality occurs, it might therefore be an inadvertent consequence of the behaviour rather than the motive for it. Our observations suggest that males who commit infanticide are unlikely to gain direct fitness benefits. Evidence does not fit the sexual selection hypothesis. Aggression towards calves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Male botos are known to perform agonist behavior against conspecifics and other aquatic animals. Reports of direct aggression toward boto calves (Bowler et al, 2018;da Silva et al, 2021) have been reported. However, most of these known attacks did not result in the death of the calf, suggesting that mortality would be an inadvertent consequence of the aggressive behavior rather than the motive.…”
Section: Behavior Socio-sexual Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Male botos are known to perform agonist behavior against conspecifics and other aquatic animals. Reports of direct aggression toward boto calves (Bowler et al, 2018;da Silva et al, 2021) have been reported. However, most of these known attacks did not result in the death of the calf, suggesting that mortality would be an inadvertent consequence of the aggressive behavior rather than the motive.…”
Section: Behavior Socio-sexual Behaviormentioning
confidence: 99%
“…However, most of these known attacks did not result in the death of the calf, suggesting that mortality would be an inadvertent consequence of the aggressive behavior rather than the motive. Males engaging in this behavior likely do not gain direct fitness benefits in terms of an accelerated return of females to reproductive condition (da Silva et al, 2021).…”
Section: Behavior Socio-sexual Behaviormentioning
confidence: 99%
“…Several techniques for capturing and handling white whales (Delphinapterus leucas) and other small odontocetes have been described. Seine nets have been used to capture species such as bottlenose dolphins (Tursiops truncatus 2Asper, 1975), killer whales (Orcinus orca) and botos, or Amazon River dolphins (Inia geoffrensis 2da Silva and Martin, 2000). Breakaway hoop nets have been successfully used in capturing bottlenose dolphins and porpoises (Ridgway, 1966;Asper, 1975;Hanson, 1998).…”
Section: Capturementioning
confidence: 99%
“…comm.). In contrast to most odontocetes, botos are much more comfortable laying on their side than on their bellies and consequently struggle less (da Silva and Martin, 2000). Tucuxis (Sotalia fluviatilis), however, are more nervous than botos when being handled (Martin, pers.…”
Section: Capturementioning
confidence: 99%
See 1 more Smart Citation